Răspuns :
a / 5 = b / 3 = k ⇒ a = 5k si b = 3k
stiim ca a² - b² = 64 ⇔ (5k)² - (3k)² = 64
25k² - 9k² = 64
16k² = 64
k = √ (64:16) = √4 = 2
R: a = 5*2=10 si
b = 3*2 = 6 .
stiim ca a² - b² = 64 ⇔ (5k)² - (3k)² = 64
25k² - 9k² = 64
16k² = 64
k = √ (64:16) = √4 = 2
R: a = 5*2=10 si
b = 3*2 = 6 .
{a, b} dp{5,3}
a²-b²=64
a/5=b/3=k
a=5k
b=3 k
(5k) ²-(3k) ²=64
25k²-9k²= 64
16k²=64 |: 16
k²= 4
k=√4
k=2
a=5×2=10
b=3×2=6
a²-b²=64
a/5=b/3=k
a=5k
b=3 k
(5k) ²-(3k) ²=64
25k²-9k²= 64
16k²=64 |: 16
k²= 4
k=√4
k=2
a=5×2=10
b=3×2=6